Manejo de azevém (Lolium multiflorum Lam.) resistente ao glyphosate com o uso de diferentes herbicidas - Stasievski, Angelo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The overall objective of this study was to evaluate management alternatives ryegrass resistant to glyphosate, by using ACCase inhibitors, photosystem I, and glutamine synthetase in three distinct growth stages (tillering, booting and early flowering ), as well as the effect of sequential application of paraquat, and the residual effect (carry-over) of these herbicides to corn. For the information required, it was conducted three studies, and the Study 1 aimed to characterize or define the degree of resistance of ryegrass population to glyphosate, when the herbicide was applied at different growth stages. The Study 2, aimed at verifying the effectiveness of different herbicides in controlling the resistant ryegrass to glyphosate. The Study 3, aimed to determine the potential for phytotoxicity of ACCase inhibitor herbicide to corn when applied 0, 5, 10 and 15 days prior to sowing, in both soils, sandy clay loam and clay. In the first study, it was determined the resistance factor (RF) of the glyphosate-resistant ryegrass population in experiments of dose response curves. The treatments consisted in the application of glyphosate at doses: 0, 45, 90, 180, 360, 720, 1440, 2880, 5760, and 11520 g a.e.ha-1, on susceptible and potentially resistant ryegrass populations, in three phenological stages. The second study consisted of three experiments and was aimed to evaluate the herbicidal effect on the management of ryegrass applied in three distinct stages, as well as the effect of sequential application of paraquat (300 g a.i.ha-1). The treatments consisted of glyphosate at 1080, 1440 and 1800 g a.i.ha-1; clethodim: 72, 96 and 120 g a.i.ha-1; tepraloxydim: 75, 100 and 125 g a.i.ha-1, haloxyfop-p-methyl: 45, 65 and 75 g a.i.ha-1, quizalofop-p-ethyl: 56.25, 75 and 93.75 g a.i.ha-1, fluazifop-p-butyl: 187.5; 250 and 312.5 g a.i.ha-1, paraquat: 225, 300 and 375 g a.i.ha-1; gluphosinate: 300, 400 and 500 ...

O objetivo geral do presente trabalho, foi avaliar alternativas de manejo de azevém resistente ao herbicida glyphosate, através do uso de herbicidas inibidores da ACCase, do fotossistema I, e da glutamina sintetase, em três estádios fenológicos (perfilhamento, emborrachamento e início do florescimento), assim como, o efeito da aplicação sequencial de paraquat, e o efeito residual (carry over) destes herbicidas à cultura do milho. Para isso, foram conduzidos três estudos: o Estudo 1 visou caracterizar ou definir o grau de resistência da população de azevém ao glyphosate, quando o herbicida foi aplicado em diferentes estádios fenológicos, o Estudo 2, que visou verificar a eficácia de diferentes herbicidas no controle do azevém resistente ao glyphosate, e o Estudo 3, teve como objetivo verificar o potencial de fitointoxicação de herbicida inibidores da ACCase à cultura do milho, quando aplicados 0, 5, 10 e 15 dias anterior a semeadura, em dois tipos de solos, franco argilo arenoso e argiloso. No primeiro estudo, foi determinado o Fator de Resistência (FR) da população de azevém resistente ao glyphosate em experimentos de curvas de dose resposta. Os tratamentos foram constituídos da aplicação de doses do herbicida glyphosate: 0, 45, 90, 180, 360, 720, 1440, 2880, 5760, e 11520 g e.a.ha-1, em populações de azevém suscetível, e potencialmente resistente, em três estádios fenológicos. O segundo estudo, foi constituído por três experimentos e visou avaliar o efeito de herbicidas no manejo do azevém, aplicados em três estádios distintos de desenvolvimento, assim como o efeito da aplicação sequencial de paraquat (300 g i.a.ha-1). Os tratamentos foram constituídos da aplicação de doses do herbicida glyphosate: 1080, 1440, 1800 g e.a.ha-1; clethodim: 72, 96, 120 g i.a.ha-1, tepraloxydim: 75, 100, 125 g ...
Management to glyphosate - resistant italian ryegrass (lolium multiflorum lam.), with the use of different herbicides
Keywords: Azevem - Manejo; Erva daninha - Controle; Resistência a herbicidas; Milho - Resíduos herbicidas; Herbicide injuries